2014
DOI: 10.1039/c4cp02733g
|View full text |Cite
|
Sign up to set email alerts
|

High voltage hybrid organic photovoltaics using a zinc oxide acceptor and a subphthalocyanine donor

Abstract: We demonstrate hybrid organic photovoltaic (HOPV) bilayer devices with very high open circuit voltages (VOC) of 1.18 V based on a sol-gel processed zinc oxide (ZnO) acceptor and a vacuum deposited boron subphthalocyanine chloride (SubPc) donor layer. X-ray photoelectron spectroscopy (XPS) and Kelvin Probe (KP) measurements of the ZnO/SubPc interface show that the ZnO preparation conditions have a significant impact on the film composition and the electronic properties of the interface, in particular the work f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In hybrid bulk heterojunctions, one organic component, for example, the fullerene derivative, is replaced by inorganic nanoparticles or quantum dots, while the other one remains organic in nature (polymer) . The hybrid devices with a classical (flat, non‐structured) heterojunction attract less attention currently, since their characteristics are generally inferior to those of fully organic congeners …”
Section: Introductionmentioning
confidence: 78%
“…In hybrid bulk heterojunctions, one organic component, for example, the fullerene derivative, is replaced by inorganic nanoparticles or quantum dots, while the other one remains organic in nature (polymer) . The hybrid devices with a classical (flat, non‐structured) heterojunction attract less attention currently, since their characteristics are generally inferior to those of fully organic congeners …”
Section: Introductionmentioning
confidence: 78%
“…This suggests that the band offset between ZnO and In 2 O 3 may cause charge transport in the bilayer structure. Given that ZnO has a lower Fermi level (approximately 3.2 eV) than that (approximately 4.3 eV) of In 2 O 3 [28,29], it is possible that electrons in the Fermi level of ZnO migrate to that of In 2 O 3 in the bilayer structure, as depicted in Figure 7a. In consequence, the electron migration from ZnO into In 2 O 3 will deplete the electrons near the surface of the underlying ZnO film and then the electron-depletion layer will be positively charged.…”
Section: Resultsmentioning
confidence: 99%
“…[13,14] The preparation of the archetypal photovoltaic cell was similar to that previously reported. [18,19] The cell scheme was 'glass/ ITO/MoO x /SubPcH 12 /acceptor/Al', where MoO x is a 10 nm substoichiometric molybdenum trioxide layer (buffer/workfunction modifier, [1,[5][6][7][8]19] see Figure S1), acceptor = SubPzS 3 F 0 , SubPzS 2 F 4 , SubPzS 1 F 8 , SubPcF 12 (or C 60 , see text), and Al is an aluminum top cathode (40 nm). The thickness of a p-type layer (SubPcH 12 ) was 20 nm, the thickness of an n-type (acceptor) layer was 30 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Parent compound, unsubstituted subphthalocyaninatoboron(III) chloride is routinely utilized as a donor in the devices containing molecular [5,6] or hybrid [7] heterojunctions, but can also serve as an acceptor in conjunction with the electronrich molecular materials, such as polyarenes or thiophenes. [8] It was recently shown that even without p/n junction subphthalocyanines give higher yields of free charge carriers upon photoexcitation than other molecular semiconductors.…”
Section: Introductionmentioning
confidence: 99%